Sustainability in empowering mumpreneurs through Islamic social finance - Mohd Yusoff, Syarah Syahira; Kassim, Salina; Hassan, Rusni (Routledge, 2024)
Sustainable finance refers to investment choices that include a project's environmental, social, and governance (ESG) implications. The utilization of sustainable resources and climate change mitigation are environmental considerations. The rights of people and animals, consumer protection, and a range of employment procedures, on the other hand, are all social elements, whereas governance considerations pertain to the management, employee relations, and compensation policies of both public and private organizations. Islamic sustainable finance (ISF) has been the “tittle-tattle” in the finance industry of late. Many Islamic banks have taken an initiative by offering new products that are ESG (environmental, social, governance) friendly. Without a doubt, ISF is a comprehensive approach to overcoming global ESG issues and addressing specific ESG issues. Islamic social finance (iSoFi), which is the subset of ESG, are closely related especially on the social side. Focusing on the livelihood of the women entrepreneur in the B40 society, it is vital for the industry to map out the capacity of ISF in ensuring the sustainability of the mumpreneurs. It is submitted that with a better financial literacy, this focal group will be better sustained.